Numerical investigation of mixed convection and viscous dissipation in couple stress nanofluid flow: A merged Adomian decomposition method and Mohand transform - Khader Mohamed M.; Adel Mohamed; Messaoudi Mohamed (Open Physics)
This work focuses on the impact of a magnetic field and viscous dissipation on the mixed convective flow of a couple stress nanofluid over a sheet that is stretching linearly. The research focuses on how these variables impact the model’s overall heat transfer characteristics and the fluid’s behavior. The sheet’s stretching causes the fluid to move as it extends, which is what causes the flow. When considering a heating procedure at the prescribed surface temperature, the heat transmission problem has been examined. The modified Adomian decomposition method (ADM) is a computational method that simplifies the complex governing equations of the model under study and finds their numerical solutions. This technique uses the Mohand transform in conjunction with the ADM, which ensures a high degree of convergence, producing a series solution that closely resembles the exact solution to the problem. In addition, we evaluate the residual error function to satisfy the effectiveness and accuracy of the introduced technique. When the current findings were compared with other methods for particular flow scenarios, they demonstrated strong agreement, confirming the accuracy of the solution. A complete examination of the effects of the different parameters has been provided, including graphic and tabular illustrations of the effects. Additionally, a comparison chart illustrating the agreement between the two sets of data has been given to show the coherence between the present numerical outcomes and previously published findings.